1996
DOI: 10.1152/jappl.1996.80.6.2250
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial enzymes increase in muscle in response to 7-10 days of cycle exercise

Abstract: Endurance exercise training induces a significant increase in the respiratory capacity of skeletal muscle. This is reflected by a training-induced increase in mitochondrial enzyme activity. One consequence of this adaptation is that there is a decreased reliance on carbohydrate utilization with a concomitant increase in fat utilization, resulting in an improvement in endurance capacity. Recently it has been reported that 7-14 days of cycle ergometer exercise training does not induce an increase in mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
128
1
6

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(166 citation statements)
references
References 0 publications
29
128
1
6
Order By: Relevance
“…However, aforementioned studies show that even modest endurance training increases VO2max to some extent. Furthermore, other studies have also shown a 5 to 10% improvement in VO2max and increases in mitochondrial enzyme level with only a short-term endurance training program (Mier et al 1997;Hickson 1981;Spina et al 1996). Recently very low volume high-intensity interval training (all-out exercise efforts above 100% of peak workload) has been proposed as a novel, time-effective exercise regime for improving VO2max (Saanijoki et al 2015;Burgomaster et al 2007).…”
Section: Physical Activitymentioning
confidence: 99%
“…However, aforementioned studies show that even modest endurance training increases VO2max to some extent. Furthermore, other studies have also shown a 5 to 10% improvement in VO2max and increases in mitochondrial enzyme level with only a short-term endurance training program (Mier et al 1997;Hickson 1981;Spina et al 1996). Recently very low volume high-intensity interval training (all-out exercise efforts above 100% of peak workload) has been proposed as a novel, time-effective exercise regime for improving VO2max (Saanijoki et al 2015;Burgomaster et al 2007).…”
Section: Physical Activitymentioning
confidence: 99%
“…11 CS activity correlates highly with in vitro measurements of skeletal muscle mitochondrial oxidative capacity 26 and has been commonly used as a marker of muscle oxidative capacity. 27,28 Histochemical staining Serial cross-sections 10 mm thick were cut from the mounted muscle sample in a cryostat maintained at 7 20 C. The sections for fibre typing were preincubated at pH 4.30 and 4.54, and were classified as either type I, IIa or IIx according to the acid lability of different isoforms of myosin adenosine triphosphatase. 25 For each subject, a mean ( AE s.d.)…”
Section: Slow Component Of V á O 2 Kineticsmentioning
confidence: 99%
“…However, linear stepwise regression revealed that the magnitude of the relative SC of the Tr group was best explained by CS activity alone, with CS explaining 77% of the variance of the magnitude of the relative SC. CS activity is a marker of muscle oxidative capacity 27,28 and these correlations imply that the greater the CS activity, the smaller will be the size of the relative SC for endurance trained subjects. Although these findings do not indicate a causal link, it is reasonable to speculate that the lower SC is in response to an increase in the oxidative capacity of the contracting muscle.…”
Section: Slow Component Of V á O 2 Kineticsmentioning
confidence: 99%
“…It has been extensively used as a metabolic marker in assessing oxidative and respiratory capacity (22). More than 30 years ago, Holloszy and his colleagues (8) reported that endurance exercise training increases the oxidative enzyme activities in skeletal muscle.…”
mentioning
confidence: 99%
“…More than 30 years ago, Holloszy and his colleagues (8) reported that endurance exercise training increases the oxidative enzyme activities in skeletal muscle. After that, numerous studies were conducted to examine the effect of exercise training on muscle oxidative capacity and metabolic characteristics (7,15,20,22,29). It is generally recognized that the skeletal muscle oxidative capacity and the activities of mitochondrial enzymes are elevated by endurance exercise training.…”
mentioning
confidence: 99%